2017
DOI: 10.1007/s12026-016-8887-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of MSCT angiography in early detection of lower limb arterial lesions in patients with antiphospholipid syndrome

Abstract: Antiphospholipid syndrome (APS) is an autoimmune disease which is characterized by arterial and venous thromboses, fetal loss, and the presence of antiphospholipid antibodies in the serum. It is characterized by accelerated atherosclerosis. Increased tendency towards thrombosis leads to the occurrence of various vascular events. The objective of our study was to determine if there are subclinical changes on lower limb arteries in APS patients and what the best diagnostic choice for their establishment is. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…By comparing our results with previous findings, we have shown that MDCTA is a superior method compared to DUS, which cannot be used to visualise smaller blood vessels and cannot provide the precise quantitative and qualitative characteristics of the atheromatous plaque under examination [23][24][25][26]. Invasive angiography was, despite its possible complications during and after the procedure, until recently, the gold standard.…”
Section: Discussionmentioning
confidence: 64%
“…By comparing our results with previous findings, we have shown that MDCTA is a superior method compared to DUS, which cannot be used to visualise smaller blood vessels and cannot provide the precise quantitative and qualitative characteristics of the atheromatous plaque under examination [23][24][25][26]. Invasive angiography was, despite its possible complications during and after the procedure, until recently, the gold standard.…”
Section: Discussionmentioning
confidence: 64%
“…In the absence of histopathology, it may be difficult to distinguish APL-related thrombosis of another concomitant atherosclerotic occlusions from vasculitis of peripheral vessels, and clinicians must be guided purely by clinical presentation [19].The available evidence shows that subclinical changes in the lower extremities arteries in patients with APS are more common than in healthy subjects, and 64-slice CT-angiography with contrast is the method of choice for monitoring disease progression [20]. In the present case, the CT angiography did not show stenosis, atheroma plaques, or signs of thrombosis in the arterial system of the affected foot; however, a drastic decrease in the caliber of the posterior tibial artery of the right extremity was observed without filling in the plantar arteries, although without clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Saponjski et al [14] used 64-multi-sliced computed tomography to analyse lower limb vascular lesions and found a high prevalence of vascular lesions in patients with APS. They argue that this technique may be more accurate than ultrasound, but the downside is the use of radiation.…”
Section: Editorialmentioning
confidence: 99%